Harian Pedoman: Media Ekspresi Ideologis Partai Sosialis Indonesia Menjelang Pemilu 1995 - Ibnu Aghniya; Dewi Yuliati (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
This article contains a discussion of the role of the Pedoman daily in voicing the ideology of democratic socialism of the Indonesian Socialist Party (PSI) during the 1955 election campaign. The Pedoman daily was one of the largest newspapers at that time which was heavily influenced by the idea of PSI socialism. This is inseparable from the figure of Rosihan Anwar as editor in chief, who has political tendencies towards PSI. This study uses historical methods to reveal the daily progress and roles of the Pedoman for PSI during the 1955 election campaign period.